Plasmapheresis in Neurological Disorders: Frequency and Type of Adverse Effects Associated with this Procedure in Atertiary Care Hospital in Pakistan - Kazmi, Syed Sakhawat; Alamgir, Waseem; Hashmat, Asif; Yousaf, Ali; Nawaz, Khurram Haq; Hassan, Zahid (Pakistan Armed Forces Medical Journal, 2022)
Objective: To determine the frequency and type of adverse effects associated with plasmapheresis among the patients with neurological disorders at a tertiary care hospital in Pakistan. Study Design: Prospective longitudinal study. Place and Duration of Study: Pak Emirates Military Hospital, Rawalpindi Pakistan, from Jan to Jun 2019. Methodology: The sample population comprised 150 patients with various neurological disorders requiring plasmapheresis at a tertiary care hospital in Rawalpindi, Pakistan. The consultant neuro physician diagnosed the underlying disorder, and a management plan of plasmapheresis was given after the departmental meeting. The presence of adverse effects was observed during the session of plasmapheresis till 48 hours after the session. Results: Out of 150 patients with neurological illness undergoing plasmapheresis at our department, 18 (12%) developed one or more adverse effects due to the procedure, while 132 (88%) did not experience any adverse effects. The mean age of the patients was 30.2 ± 2.698 years. GB syndrome 61 (40.6%) was the commonest disease for which plasmapheresis was done. Allergic reaction 4 (2.6%) was the commonest side effect among the patients undergoing plasmapheresis, followed by abdominal pain 3 (2%). 146 (97.4%) patients were shifted toward, and 4 (2.6%) required intensive care unit admission after the procedure due to complications. Mortality due to this procedure was nil in the given period. Conclusion: Plasmapheresis is a relatively safe procedure for neurological illnesses with an immunological basis. Patients should be told about the common adverse effects they could face during the procedure especially allergic reactions and...